2004
DOI: 10.1023/b:biry.0000040224.47278.3b
|View full text |Cite
|
Sign up to set email alerts
|

Study of Secondary Specificity of Enteropeptidase in Comparison with Trypsin

Abstract: A comparative study of secondary specificities of enteropeptidase and trypsin was performed using peptide substrates with general formula A-(Asp/Glu)n-Lys(Arg)-(downward arrow)-B, where n = 1-4. This was the first study to demonstrate that, similar to other serine proteases, enteropeptidase has an extended secondary binding site interacting with 6-7 amino acid residues surrounding the peptide bond to be hydrolyzed. However, in the case of typical enteropeptidase substrates containing four negatively charged As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…1). Experiments with synthetic peptides and protein substrates indicated that the acidic residues are required for enteropeptidase recognition and cleavage (1)(2)(3)(4)(5)(6)(7). Due to its highly specific extended subsite interactions, in analogy to restriction endonucleases, enteropeptidase became known as a restriction protease, and the Asp-Asp-Asp-Asp-Lys recognition site has been widely utilized as a protein engineering tool for the specific cleavage of fusion proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Experiments with synthetic peptides and protein substrates indicated that the acidic residues are required for enteropeptidase recognition and cleavage (1)(2)(3)(4)(5)(6)(7). Due to its highly specific extended subsite interactions, in analogy to restriction endonucleases, enteropeptidase became known as a restriction protease, and the Asp-Asp-Asp-Asp-Lys recognition site has been widely utilized as a protein engineering tool for the specific cleavage of fusion proteins.…”
mentioning
confidence: 99%
“…In accordance with structural predictions, mutation of Lys 99 in the catalytic subunit of enteropeptidase abolished trypsinogen activation. Although the crystal structure suggested an important role for at least 3 of the 4 Asp residues in enteropeptidase recognition, a number of studies using various protein substrates or synthetic peptides indicated that a minimal recognition sequence for enteropeptidase consists of a Lys/Arg at P1 and an Asp/Glu at P2, whereas the P3-P5 acidic residues might enhance activity (1)(2)(3)(4)(5)(6)(7). Consistent with the critical role of the P2 Asp was the recent observation that the D22G mutant of human cationic trypsinogen was resistant to activation by bovine enteropeptidase (9).…”
mentioning
confidence: 99%
“…Despite the replacement of three aspartic acid residues in P3 P5 positions with glycine residues [15], the third investigated peptide, G 5 DK F(NO 2 )G, which unexpectedly appeared as a very efficient enteropeptidase substrate, was hydrolyzed by all three enteropeptidase forms (including the natural full length enzyme) with vir tually the same efficiency both in the absence and in the presence of calcium ions (Table 1). In this case, it is worth mentioning that all the results regarding the hydrolysis of substrates with D 4 K truncated enteropeptidase forms and also in all cases of hydrolysis of the substrate with one aspartic acid residue ( G 4 DK ) indicate insignificant inhibition by calcium ions.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide substrates GD 4 K F(NO 2 )G, G 5 DK F(NO 2 )G, LTAEEKA, and LTAEEKAAV were synthe sized according to the earlier described techniques [15].…”
Section: Methodsmentioning
confidence: 99%
“…Previous specificity studies using synthetic peptides and protein substrates have indicated that acidic residues are required for recognition and cleavage by enteropeptidase. [2][3][4][5][6][7][8] In these studies, however, the relative importance of the respective Asp residues was not quantitatively or systematically analyzed, although P2 and P3 Asps were indicated to be most important, in addition to P1 Lys. The crystal structure of the recombinant bovine enteropeptidase light chain coupled with an inhibitor, an analog of the trypsinogen activation peptide, was elucidated.…”
mentioning
confidence: 99%